Colorism Awareness im Literaturunterricht der Grundschule (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2025)
Colorism Awareness is a current challenge for both learners and teachers. This exploratory study conducted in a German primary school shows that critical literacy education must diversify the books teachers choose to read in favor of the visibility of marginalized groups. By engaging with the own-voices-picture book „Sulwe” (2021), the students dealt with the discrimination against people of different appearances, known as colorism, and the devaluation of skin tones considered dark. The study addresses the desideratum of establishing Colorism Awareness as a long-term goal in primary school didactics.
Keywords: Colorism Awareness; picture book; critical literacy; teacher education